Allelopathic potential of etlingera coccinea (B.) sakai & nagam on seed germination and growth of mung bean and siam weed / Mohamad Nadzrin Mohamad Zainurin ...[et al.] - Mohamad Zainurin, Mohamad Nadzrin; Harman, Nurfitri; Jasnie, Farnidah; Wai, Lo Chor (Faculty of Applied Sciences, 2021)
Etlingera coccinea, a native Borneon Zingiberaceae are found to exert allelopathic effect on some weed species. The objective of this study is to investigate the allelopathic effects of hexane (80%), methanol (80%), ethyl acetate (80%) extracts from the dried powder of both stem and leaf of E. coccinea on mung bean (Vigna radiata) and Siam weed (Chromolaena odorata). The phytochemical screening of both stem and leaf crude extracts elicited saponin, tannin, flavonoid, and terpenoid, which are targeted bioactive compounds for allelopathy. The allelopathic activity was assessed by evaluating their effects on seed germination and percentage of radicle and shoot growth. The results showed that both stem and leaf extracts have a suppressive effect on the mung bean development during in-vitro bioassay. The methanolic extracts of both stem and leaf showed the most significant suppression (100%) than other solvent extracts. In the pot experiment, the methanolic stem extracts suppressed the Siam weed's germination by 57 ± 0.13% and the methanolic leaf extracts suppressed the growth by 46 ± 0.29%. The present study shows that E. coccinea methanolic extract has the potential as bio-herbicide.